(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2018)
In our orthodontic practice we have seen a recent spurt of increasing numbers of young adults who desire cost effective, non surgical correction of malocclusion and accept dental camouflage as a treatment option to mask the skeletal discrepancy. Usually over 10 mm overjet with traumatic bite is very difficult to treat without extraction; therefore this case is handling so carefully that the upper central incisors cannot loose or dead because of excessive force. In this case patient growth is complete and therefore the only option is fixed orthodontic treatment. So here the challenge is reduction of overjet and correction of traumatic bite without any extraction and is careful to save the tooth vitality. Following treatment marked improvement in patient’s smile, facial profile and lip competence were achieved and there was a remarkable increase in the patient’s confidence and quality of life. Ban J Orthod & Dentofac Orthop, April 2015; Vol-5 (1-2), P.30-32